Analisis Deskriptif Masalah Kesehatan Pada Nelayan di Desa Kemojan, Karimun Jawa, Jepara - Ratih Pramitasari; Haikal Haikal; Yoni Setyo Nugroho Bayu (Dian Nuswantoro Semarang, 2022)
Background: Indonesian population 58.22% work in the informal sector where on average 33% work as farmers and fishermen. This underlies the importance of paying attention to the informal sector in terms of occupational health. Karimun Jawa region at least 60% of the population work as fishermen and traditional divers.Method: This type of descriptive research with the aim to describe the condition of the description of health problems experienced by fishermen in Kemojan village with a sample of 21 fishermen with research instruments in the form of questionnaires, HB quick check, tensimeter, and urine color sample tests.Results: Respondent's blood pressure showed a systolic pressure that was more than normal or more than 121mmHg of 81% of the total 21 respondents and 47.6% had a diastole level that was more than normal, with 32% of respondents having higher levels of hemoglobin abnormal and 61.9% experiencing moderate dehydration.Conclusion: Respondent's blood pressure showed a tendency to experience hypertension, and lack of consumption of mineral water. Divers of fisherman respondents are advised to be able to control salt consumption to reduce the potential risk of hypertension and increase consumption of mineral water so that respondents avoid interference with the excretion channels in the body.